Arts, religion, and the environment: exploring nature's texture - Bergmann, Sigurd; Clingerman, Forrest (Studies in environmental humanities, 2018)
Humans have been described as "meaning-making animals." At the threshold of the Anthropocene, how might humans artistically envision their place in the world? Do humans possess cultural tools, which will allow us to imagine new possibilities and relationships with the natural environment at a time when our material surroundings are under siege?0Exploring Nature's Texture looks at the imaginative possibilities of using the visual arts to address the breakdown of the human relationship with the environment. Bringing together contributions from artists, theologians, anthropologists and philosophers, it investigates the arts as a bridge between culture and nature, as well as between the human and more-than-human world. Contributors: Whitney A. Bauman, Sigurd Bergmann, Forrest Clingerman, Timothy M. Collins, J. Sage Elwell, Reiko Goto, Arto Haapala, Tim Ingold, Karolina Sobecka, George Steinmann